Metode Pemilihan Material Tabung CNG Menggunakan Metode Performace Indexes - Bangkit Indriyana; Christian Wely Wullur (Musamus Journal of Electro & Mechanical Engineering, 2019)
The compressed natural gas (CNG) cylinder pressure vessel become important in NGV fuel driving system because demand in CNG base as increase. The selection of material should be made effectively to reduce cost and to improve properties of the vessel. The choice of material cannot be made independently of the choice of process by which the material is to be formed, assemblied, finished, and otherwise treated. Cost enters, both in the choice of material and in the way the material is processed. Fully metal CNG pressure vessel is cheap but it is the heaviest pressure vessel compare to other materials. Composite has become an alternative material for CNG pressure vessel since it properties can be modified based on market needed. In this paper, the process of material selection for CNG pressure vessel using performance indexes have been analyzed. The result showing that material AA 6061-T6/S-Glass full wrapped has the highest Performance Indexes point.